Trajectories of antidepressant use and 6-year change in body weight: a prospective population-based cohort study - Lassale, Camille; Lugon, Gabriela; Hernáez, Álvaro; Frank, Philipp; Marrugat, Jaume; Ramos, Rafael; Garre-Olmo, Josep; Elosua, Roberto (Frontiers in Psychiatry, 2024)
BackgroundAntidepressant drug treatment may be associated with weight gain, but long-term studies are lacking.MethodsWe included 3,127 adults (1,701 women) from the REGICOR study, aged 55.6 (SD = 11.6) years on average in 2003–2006, living in the northeast of Spain. They had data at two time points (baseline and a median of 6.3 years later) on self-reported antidepressant use, body weight and height, and on baseline smoking, physical activity, diet quality, education, civil status, and depressive symptoms assessed with the Patient Health Questionnaire (PHQ-9) at follow-up. We defined four trajectories of antidepressant use as follows: never use, new use at follow-up, initial use discontinued, repeated use at both time points. We used multivariable linear models to estimate the association of these trajectories with the percentage of weight change. In people without obesity at baseline (n = 2,404), we also estimated the association with obesity incidence at follow-up.ResultsThe average 6-year weight gain was 0.53 kg (1.01% body weight), and 24.5% of the participants gained >5% of body weight. The majority (83.6%) of participants did not report any use of antidepressants, 6.2% initiated during follow-up, 5.1% discontinued it, and 5.1% reported their use at both time points. In multivariable analyses, compared to never users, all trajectories were associated with greater weight gain: +1.78% (0.57, 2.98) for initial use discontinued, +2.08% (0.97, 3.19) for new use at follow-up, and +1.98% (95% CI: 0.75, 3.20) for repeated use. In non-obese participants at baseline (n = 2,404), the odds ratio for becoming obese was 2.06 (1.03, 3.96) for repeated use and non-statistically significant for the other trajectories.ConclusionsIn a population-based adult cohort, repeated use of antidepressants was strongly associated with weight gain. New and discontinued use was associated with weight gain, but non-significantly to obesity incidence. Given the global obesity epidemic and the widespread use of antidepressants, weight management and metabolic monitoring should be encouraged and integrated into depression follow-up guidelines alongside antidepressant prescriptions.